2006
DOI: 10.1016/j.clpt.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine intake and dose response when smoking reduced–nicotine content cigarettes

Abstract: Our study suggests that reduced-nicotine content cigarettes are reasonable candidates for trying to reduce the level of nicotine addiction in smokers. The flat nicotine dose-cardiovascular response curve is consistent with other studies demonstrating tolerance to the cardiovascular effects of nicotine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 15 publications
13
82
0
2
Order By: Relevance
“…That most smokers compensate little or not at all when the nicotine content of cigarette tobacco is reduced in the absence of changes in tar and other characteristics of the cigarette was observed in another study of smoking single cigarettes with variable nicotine content conducted in our laboratory (23), as well in a study by Rose et al (24). If the smoker finds it is very difficult to extract nicotine from a cigarette, he or she may give up trying and accept lower doses of nicotine, gradually reducing their level of dependence.…”
Section: Discussionsupporting
confidence: 67%
“…That most smokers compensate little or not at all when the nicotine content of cigarette tobacco is reduced in the absence of changes in tar and other characteristics of the cigarette was observed in another study of smoking single cigarettes with variable nicotine content conducted in our laboratory (23), as well in a study by Rose et al (24). If the smoker finds it is very difficult to extract nicotine from a cigarette, he or she may give up trying and accept lower doses of nicotine, gradually reducing their level of dependence.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, HS-Nicotine yield can be estimated from the HST time and the correlation between smoking time and smoke nicotine yield obtained from a machine-smoking regime. As demonstrated in this study, in line with the results of other publications (22,29), the exposure depends essentially on the speed at which the cigarette is smoked. An increase of the human smoking intensity, resulting in a decrease in smoking time, generates an increase of smoke exposure, whatever the puff number, puff duration, puff volume and filter ventilation open or blocked.…”
Section: Estimation Of Human Smoking Nicotine Yields Using Smoking Timesupporting
confidence: 91%
“…In addition, a 2-day study found an initial increase in puff behavior, which dissipated after several smoking bouts (56). Two studies have examined changes in smoking behavior measured for a single cigarette, one of which found no differences in puff number (12), the other found significantly lower puffing intensity for all 3 Quest brands compared with usual brand smoking (36). Overall, this findings add to the evidence that smokers do not respond or compensate for cigarettes with markedly reduced nicotine content and that any initial attempts dissipate over repeated use (37).…”
Section: Smoking Behaviormentioning
confidence: 99%
“…Use of cigarettes with very low nicotine content seem to result in genuine reductions in nicotine delivery and attenuate physiological effects of nicotine, such as increases in heart rate and EEG activity (11)(12)(13)(14)(15)(16)(17). De-nicotinized cigarettes have also been found to reduce symptoms of nicotine withdrawal normally associated with tobacco abstinence (11,15,(17)(18)(19)(20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation